Gammarus inaequicauda Stock, 1966 in Norway (Crustacea, Amphipoda) - Wim Vader; Carlos G. Christophersen; Jochen Kempe; Arnfinn Skadsheim (Fauna Norvegica, 1984)
The amphipod Gammarus inaequicauda Stock, 1966, earlier in Norway only known from Sars' vague type-locality 'Moss, Christianiafjord', has been found at several localities in the Oslo fjord and along the Skagerak coast of southern Norway. All Norwegian localities are shallow, densely vegetated protected inshore habitats, with salinities at least periodically below that of the open coast. Common associated crustaceans are the amphipods Corophium insidiosum Crawford, Ericthonius brasiliensis (Dana), Microdeutopus anomalus Rathke, M. gryllotalpa (Dana) and Phtisica marina Slabber, and the isopod Idotea chelipes (Pallas).